2018
DOI: 10.1038/s41598-018-28488-6
|View full text |Cite
|
Sign up to set email alerts
|

Naturally derived Heme-Oxygenase 1 inducers attenuate inflammatory responses in human dendritic cells and T cells: relevance for psoriasis treatment

Abstract: Psoriasis is a chronic autoimmune disease mediated by dysregulated immune responses in dendritic cells (DC) and T cells. The stress-response enzyme heme oxygenase-1 (HO-1) has been described as protective in animal models of psoriasis, however, implementation of HO-1-based therapies is hindered by the lack of clinically-suitable HO-1 inducers. The plant-derived polyphenols, carnosol and curcumin, have been identified as candidate HO-1 inducers however there has been little investigation into their effects on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 65 publications
7
45
0
Order By: Relevance
“…The regulation of metabolism by the two polyphenols is via activation of AMPK, which results in the inhibition of mTOR signaling [ 18 ]. Carnosol and curcumin also upregulate heme oxygenase-1 (HO-1), which is an important anti-inflammatory and antioxidant enzyme [ 232 ]. Recently, an untargeted metabolomics study has revealed the induction of anti-inflammatory prostaglandin pathway and modulation of gut microbiota by the consumption of curcumin-containing curcuma longa L. extract [ 233 ].…”
Section: Effect Of Polyphenols On the Composition Of Gut Microbiotmentioning
confidence: 99%
“…The regulation of metabolism by the two polyphenols is via activation of AMPK, which results in the inhibition of mTOR signaling [ 18 ]. Carnosol and curcumin also upregulate heme oxygenase-1 (HO-1), which is an important anti-inflammatory and antioxidant enzyme [ 232 ]. Recently, an untargeted metabolomics study has revealed the induction of anti-inflammatory prostaglandin pathway and modulation of gut microbiota by the consumption of curcumin-containing curcuma longa L. extract [ 233 ].…”
Section: Effect Of Polyphenols On the Composition Of Gut Microbiotmentioning
confidence: 99%
“…Currently, the exact cellular mechanism of HO-1 induced immunosuppressive effects is still unclear. However, studies suggest that a large component may be attributed to the ability of HO-1 and the HO-1 catalyzed end products bilirubin and CO in inhibiting dendritic cell (DC) function (31)(32)(33). A recent study demonstrated that induction of HO-1 hinders DC maturation in vitro (31).…”
Section: Heme Oxygenase-1 In Immune Regulationmentioning
confidence: 99%
“…However, studies suggest that a large component may be attributed to the ability of HO-1 and the HO-1 catalyzed end products bilirubin and CO in inhibiting dendritic cell (DC) function (31)(32)(33). A recent study demonstrated that induction of HO-1 hinders DC maturation in vitro (31). This resulted in limited antigen presentation and activation of adaptive T cell responses as DCs after HO-1 induction exhibited diminished ability to stimulate proliferation of allogeneic CD4+ T cells (31).…”
Section: Heme Oxygenase-1 In Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis shows that curcumin supplementation significantly reduces concentration of circulating IL-6, a key regulator of the immune system, with more evident effect in patients with higher degree of systemic inflammation [ 51 ], indicating that curcumin can effectively inhibit inflammation propagation. In human dendritic cells (DCs), curcumin treatment limits DC maturation, reduces proinflammatory cytokine production, and prevents induction of allospecific T cell responses [ 52 ]. In the mononuclear cells from AD patients, curcuminoid compound reverses defective phagocytosis of A β and expression depression of TLRs such as TLRs 2–4, reflecting its ability to correct immune defects [ 53 , 54 ].…”
Section: Systemic Immunity Regulation By Phytochemicals and Its Comentioning
confidence: 99%